PENGARUH TERAPI MASSAGE PLEXUS SACRALIS TERHADAP PENURUNAN TINGKAT NYERI PADA PASIEN POSTPARTUM NORMAL DI RUANG NIFAS RSD DR. SOEBANDI JEMBER (Jurnal Kesehatan dr. Soebandi, 2013)
Pain is an integral part of labor. Untolerable pain may change normal labor into pathological one. The use of Plexus Sacralis Massage technique can be an alternative of non-pharmacological method to control labor pain during postpartum/puerpurium. The objective of this study was to analyze the influence of Plexus Sacralis Massage technique in change level pain during normal postpartum in primipara and multipara. This study used quasi experiment with using interview and observation pretest and posttest design. The population was primipara and multipara patiens at normal postpartum who reported pain at Rumah Sakit Daerah dr. Soebandi Jember. Sample size was 34 responden of experimental group who met the inclusion criteria. Data were analyzed by using Wilcoxon Signed Rank with significance level <0,05. The result showed that before intervention, mother who perceived medium pain were 76,5% and low pain were 23,5%. After intervention, those who perceived low pain 73,5%, no pain pain were 26,5%. The result of statistical test had significance level of p=0,0001. in conclution, Plexus sacralis Massage technique is influence in helping the mother to decreasing of level pain during postpartum